SOCIAL AND CULTURAL OPPRESSION OF WOMEN IN INDIA - Kaur, Kawaljit (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The Women liberation movement in India began as a social reform movement in the nineteenth century. The western ideas of liberty, equality and fraternity were being imbibed by the educated elites in India through the study of English. In India the women liberation movement against patriarchal institutions of gender injustice has been weak as compared to the women’s movements in the Western and European societies. In fact, women’s fight against the oppression of patriarchy has been rather slow in emerging in India. The nineteenth century women found themselves totally suppressed and subjugated by the male patriarchal ideologies and attitudes of those times, though there was feminist identity, consciousness and also awareness of their miserable plight.